ANALISIS PENGARUH SUKU BUNGA SBI, SUKU BUNGA KREDIT DAN NILAI TUKAR TERHADAP INFLASI DI INDONESIA PERIODE TAHUN 2006–2012 - Nyimas Deviana (Department of Development Economics, Universitas Sriwijaya, 2014)
This research was aimed to identify the effect of SBI interest rate, loan interest rate and exchange rate on inflation in Indonesia. The data usedÂ in this research were quarterly data in the periods of 2006-2012. The data were analyzed qualitatively and quantitatively using multiple regression method, Ordinary least square (OLS). The research result showed that SBI interest rate variable had a negative effect on inflation as big as -1.748030, meaning that the increase of SBI interest rate was followed by the decrease of inflation rate. Loan interest rate variable had a positive effect on inflation as big as 0.966608, meaning that the increase of loan interest rate was followed by the increase of inflation rate.Â The exchange rate variable had a negative effect on inflation as big as -4.110552, This meant the increase of exchange rate was followed by the increase of inflation rate. Keywords: SBI Interest Rate, Loan Interest Rate, Exchange Rate and Inflation